Cancer’s related anxiety “Kryptonite” − a randomized control trial for the use of guided imagery and progressive muscle relaxation - Bozas, Evangelos; Androulakis, I.; Charalambous, Andreas; Giannakopoulou, Margarita (My University, 2011)
Background: Patients’ with cancer psychological well-being can be negatively influenced by the disease or the treatment, resulting in frequent hospitalizations and disruption of the patients’ daily living. This paper reports a part of a study to explore the effect of Guided Imagery (GI) and Progressive Muscle Relaxation (PMR) on the anxiety experienced by patients with prostate and breast cancer undergoing chemotherapy or/and radiotherapy. Material and Methods: A Randomized Controlled Trial was implemented with a sample size of 200 patients with breast and prostate cancer covering all the geographical regions in Cyprus. Anxiety was assessed with the Zung Self-Rating Anxiety Scale prior and post intervention. One hundred patients were randomly assigned in the control group and one hundred in the intervention group. Based on the protocol, the patients in the intervention group received 4 supervised sessions of GI and PMR at their home within a 4-week period, additionally, to daily unsupervised interventions through audiovisual aids. Guided Imagery is simply the use of one’s imagination to promote mental and physical health. The patient was led through a relaxation and imagery exercise. The first component involved reaching a state of deep relaxation through breathing and PMR techniques. During the relaxation phase, the person closes his/her eyes and focuses on releasing the feelings of tension from his/her muscles starting with the toes and working up to the top of the head. Once complete relaxation is achieved, the second component of the intervention is the imagery, where mental images (floating on a cloud) were directed to the patient. Results: The matched pair t-test was used to assess the statistical significance differences in the pre- and post-intervention scores. Comparisons were considered significant if p < 0.05. For the control group, the mean score of SAS was 58.33±7.45. For the intervention group, the SAS score was 56.28±6.39 and 42.72±6.81 before and after the intervention, respectively. For the intervention group, the difference between pre-and post-intervention scores reached the significant level (p = 0.01). Conclusions: Results showed that the GI and PMR had a significant effect on decreasing anxiety in cancer patients. Results indicated that complementary interventions have a place in an integrative system of home-based cancer care and can work side to side with conventional interventions to improve the patient’s cancer journey and overall quality of life.
Keywords: Cancer; Anxiety; Muscles